MiR-320e is a novel prognostic biomarker in colorectal cancer - Perez-Carbonell, L; Sinicrope, F A; Alberts, S R; Oberg, A L; Balaguer, F; Castells, A; Boland, C R; Goel, A (British journal of cancer, 2015)
Background: Advances in early detection and treatment have improved outcomes in patients with colorectal cancer (CRC). However, there remains a need for robust prognostic and predictive biomarkers. We conducted a systematic discovery and validation of microRNA (miRNA) biomarkers in two clinical trial cohorts of CRC patients. Methods: We performed an initial ‘discovery’ phase using Affymetrix miRNA expression arrays to profile stage III CRC patients with and without tumour recurrence ( n =50 per group) at 3-years of follow-up. All patients received adjuvant 5-fluorouracil (5-FU) plus oxaliplatin, that is, FOLFOX, treatment. During ‘validation’, we analysed miRNAs using qRT–PCR in an independent cohort of 237 stage II–IV CRC patients treated with 5-FU-based chemotherapy, as well as in normal colonic mucosa from 20 healthy subjects. Association with disease recurrence, disease-free survival (DFS) and overall survival (OS) was examined using Cox proportional hazard models. Results: In the discovery cohort, miR-320e expression was significantly elevated in stage III colon cancers from patients with vs without recurrence (95% confidence interval (CI)=1.14–1.42; P <0.0001). These results were then independently validated in stage II and III tumours. Specifically, increased miR-320e expression was associated with poorer DFS (hazard ratio (HR)=1.65; 95% CI=1.27–2.13; P =0.0001) and OS (HR=1.78; 95% CI=1.31–2.41; P =0.0003) in stage III CRC patients. Conclusions: In two clinical trial cohorts, a systematic biomarker discovery and validation approach identified miR-320e to be a novel prognostic biomarker that is associated with adverse clinical outcome in stage III CRC patients treated with 5-FU-based adjuvant chemotherapy. These findings have important implications for the personalised management of CRC patients.